2013
DOI: 10.1128/jb.01050-13
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of the P2 Phenotype in Pseudomonas aeruginosa PAO1 Strains Involves Various Mutations in mexT or mexF

Abstract: We recently demonstrated that Pseudomonas aeruginosa PAO1 undergoes a pronounced phenotypic change when introduced into the intestines of rats during surgical injury. Recovered strains displayed a specific phenotype (termed the P2 phenotype) characterized by altered pyocyanin production, high collagenase activity, high swarming motility, low resistance to chloramphenicol, and increased killing of Caenorhabditis elegans compared to the inoculating strain (termed the P1 phenotype). The aims of this study were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…We next decided to delete the nmoR gene from another PAO1 strain (the PAO1 UK strain from the University of Nottingham). This strain was described as the C-PAO1 strain by Luong et al (37). Confirming the results of Luong et al, both the wild type and the nmoR mutant had a 2-bp deletion, at positions 905 and 906 of mexT, resulting in a frameshift (see Fig.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…We next decided to delete the nmoR gene from another PAO1 strain (the PAO1 UK strain from the University of Nottingham). This strain was described as the C-PAO1 strain by Luong et al (37). Confirming the results of Luong et al, both the wild type and the nmoR mutant had a 2-bp deletion, at positions 905 and 906 of mexT, resulting in a frameshift (see Fig.…”
Section: Resultssupporting
confidence: 66%
“…Despite the fact that only one binding site for the NmoR regulator was found in the genome of PAO1, the deletion of the nmoR gene had a profound effect on the expression of many genes, as shown by the microarray experiment results presented in Table 3 and in Table S1 in the supplemental material. A recent publication highlighted the differences between PAO1 strains in different laboratories (37). The strain used in this study clearly has the P1 phenotype, characterized by the absence of an 8-bp insertion in the mexT gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this set of experiments, we used an MPAO1-P2 strain that produces a higher amount of pyocyanin compared to that of the MPAO1-P1 strain. 16 In our preliminary experiments, we found that supplementation of media with iron increases pyocyanin production in this nutrient-limited DCM media. Therefore, we supplemented DCM with 2 ÎŒ M Fe 3+ (1 ÎŒ M Fe 2 (SO 4 ) 3 ).…”
Section: Resultsmentioning
confidence: 74%
“…[7][8][9][10] Insertional inactivation has been the main method applied to G + bacteria. 11 In this method, the flanking sequences of the exogenous DNA imported into host cells and of the target gene in the chromosome of host cells are homologous.…”
Section: Introductionmentioning
confidence: 99%